DEIKSIS DALAM NASKAH FILM ALL TOO WELL - Valenziana Cristy Simatupang; Milisi Sembiring; Vivi Novalia Sitinjak (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2024)
This research is about Deixis in All Too Well movie script. The objectives of this research are to find out the types and functions of Deixis in All Too Well movie script. Therefore, this research used the theory of Yule. This research was conducted using qualitative methods. The data of this research is Dylan and Sadie’s dialogue from the All Too Well film. The results show that there are three types and three functions of Deixis in All Too Well movie script. The types of deixis found are personal deixis, spatial deixis and temporal deixis. Furthermore, the functions of deixis are pointing. This pointing is to identify the person (who), location (where) and time (when) here, which are designated as person deixis, spatial deixis, and temporal deixis.